2008
DOI: 10.1016/j.jvolgeores.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ASTER and SRTM DEM data for lahar modeling: A case study on lahars from Popocatépetl Volcano, Mexico

Abstract: Lahars are among the most serious and far-reaching volcanic hazards. In regions with potential interactions of lahars with populated areas and human structures the assessment of the related hazards is crucial for undertaking appropriate mitigating actions and reduce the associated risks. Modeling of lahars has become an important tool in such assessments, in particular where the geologic record of past events is insufficient. Mass-flow modeling strongly relies on digital terrain data. Availability of digital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 41 publications
8
66
1
3
Order By: Relevance
“…A lahar modelled on the SRTM3 DTM at the northeastern slope and with a volume of 1×10 6 m 3 affects the central part of San Agustín Atzompa while the same volume on the ASTER DTM stops 2.5 km upstream and represents no hazard for the settlement ( Fig. 9 and 10; this effect was also observed by Huggel et al, 2008). Stevens et al (2002) found similar effects concerning the flow length on different DTMs but not to that extent.…”
Section: Results Of the Laharz Modelmentioning
confidence: 75%
See 4 more Smart Citations
“…A lahar modelled on the SRTM3 DTM at the northeastern slope and with a volume of 1×10 6 m 3 affects the central part of San Agustín Atzompa while the same volume on the ASTER DTM stops 2.5 km upstream and represents no hazard for the settlement ( Fig. 9 and 10; this effect was also observed by Huggel et al, 2008). Stevens et al (2002) found similar effects concerning the flow length on different DTMs but not to that extent.…”
Section: Results Of the Laharz Modelmentioning
confidence: 75%
“…H/L ratios for the lahar modelling between 0.2 and 0.15 were used, corresponding to published case studies (Siebe et al, 1996;Vallance et al, 2001;Capra et al, 2004). The volumes of debris flows correlate with the H/L ra- tio as demonstrated for lahars at Popocatépetl volcano by Huggel et al (2008). That means that the greater the volume of a debris flow, the smaller is the corresponding H/L ratio (Legros, 2002).…”
Section: Results Of the Msf Modelmentioning
confidence: 99%
See 3 more Smart Citations